Hemolytic Anemia and Hypoxic Brain Injury following Mothball Ingestion in a G6PD Nondeficient Infant: A Case Report - Nongrum, Saahil Manna L.; Chandel, Anuragsingh B.; Varma, Ravi; Jategaonkar, Smita; Jain, Manish (Journal of Child Science, 2021)
Mothballs are a common household item used as repellents and deodorizers. They are potential hazards and rare agents of poisoning in children. They are composed mainly of naphthalene, camphor, and 1, 4-dichlorobenzene in varying amounts depending on the manufacturers. It is essential to rule out poisoning by naphthalene in children presenting with hemolysis by eliciting a proper history. Since mothballs are readily available at home, children are drawn to it because of its attractive color and its consumption is a likely possibility. This is a case of ingestional naphthalene poisoning in a 1-year-old glucose 6-phosphate dehydrogenase nondeficient male child who presented with altered sensorium and hemolytic anemia. The child developed methemoglobinemia and sustained hypoxic brain injury. He was successfully managed by oral ascorbic acid, blood transfusion, and requisite supportive treatments. We report a case of naphthalene toxicity with hemolytic anemia and hypoxic brain damage to highlight the possibility of naphthalene poisoning in young children presenting with hemolytic anemia.
Keywords: ascorbic acid; glucose 6-phosphate dehydrogenase deficiency; hemolytic anemia; methemoglobinemia; hypoxic brain injury